A map-like visualisation method based on liquid modelling. (December 2015) - Biuk-Aghai, Robert P.; Yang, Muye; Pang, Patrick Cheong-Iao; Ao, Wai Hou; Fong, Simon; Si, Yain-Whar
Abstract: Many applications produce large amounts of data, and information visualisation has been successfully applied to help make sense of this data. Recently geographic maps have been used as a metaphor for visualisation, given that most people are familiar with reading maps, and several visualisation methods based on this metaphor have been developed. In this paper we present a new visualisation method that aims to improve on existing map-like visualisations. It is based on the metaphor of liquids poured onto a surface that expand outwards until they touch each other, forming larger areas. We present the design of our visualisation method and evaluations we have carried out to compare it with an existing visualisation. Our new visualisation has better usability, leading to higher accuracy and greater speed of task performance, as well as a lower error rate. Abstract : Highlights: Geographic maps as a familiar metaphor for information visualisation. Map-like visualisation created by modelling fluids poured onto a surface. Tree-structured hierarchical data displayed in map-like form as nested areas. User evaluation demonstrates high usability and speed, and low error rate.